Knowledge of the nursing team on pressure ulcer prevention - Nariani Souza Galvão; Maria Alice Barbosa Serique; Vera Lúcia Conceição de Gouveia Santos; Paula Cristina Nogueira
ABSTRACT Objective: describe and analyze the nursing team's knowledge about classification, evaluation and measures to prevent pressure ulcers (PU) in patients hospitalized in the ICU of a teaching hospital in the city of Manaus. Method: a descriptive and exploratory study was conducted after approval by a research ethics committee. Data were collected using a validated instrument. The study sample was made up of 40 nursing staff members, of whom 14 were nurses and 26 were nursing technicians/aides. Data were analyzed through descriptive statistics and Student's t-test, with value of p<0.05. Results: the overall mean of hits was 63.4% for technicians/aides and 51.4% for nurses, with statistically significant differences between the groups only for the PU prevention category (p<0.001). Conclusion: a deficit of knowledge on PU prevention was found among nurses and nursing technicians/aides, demanding the training of these professionals.